2018
DOI: 10.1007/s00403-018-1847-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel mutation in the mechanoreceptor-encoding gene CXCR1 in patients with keloid

Abstract: Keloids are skin fibroproliferative tumors characterized by locally invasive growth of fibroblasts and excessive collagen deposition. The objective of this study is to investigate the molecular basis of the keloid scar by studying the mutation of related genes. We performed gene screening of mechanoreceptors by quantitative polymerase chain reaction (qPCR), Sanger sequencing to detect the CXCR1gene mutation, and immuno-histochemistry to determine CXCR1 protein expression. Among the genes encoding mechanorecept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Through a multistage genome-wide association study in the Japanese population, Nakashima et al determined four new susceptibility loci (rs873549, rs1511412, rs940187, and rs8032158) to keloids in three chromosomal regions (1q41, 3q22.3-23, and 15q21.3) [ 89 ]. The findings of Zhang et al identified that a novel missense mutation in the CXCR1 gene existed in keloids and heightened CXCR1 expression was associated with keloid pathogenesis [ 90 ]. Interestingly, there is evidence suggesting that the pro allele of P53 Arg72Pro polymorphism increased genetic susceptibility for keloids in the Chinese population.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Through a multistage genome-wide association study in the Japanese population, Nakashima et al determined four new susceptibility loci (rs873549, rs1511412, rs940187, and rs8032158) to keloids in three chromosomal regions (1q41, 3q22.3-23, and 15q21.3) [ 89 ]. The findings of Zhang et al identified that a novel missense mutation in the CXCR1 gene existed in keloids and heightened CXCR1 expression was associated with keloid pathogenesis [ 90 ]. Interestingly, there is evidence suggesting that the pro allele of P53 Arg72Pro polymorphism increased genetic susceptibility for keloids in the Chinese population.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…However, the possibility of mutations caused by these genes cannot be completely ruled out because the current study is mainly focused on examining the promoter, exon and the connection region between exon and intron, and pathogenic mutations may be located in other non‐coding regions (such as introns or terminal genes). At present, it has been reported that somatic point mutations of the CXCR1 gene and the CDC2L1 gene were found in KD tissues 55,56 . A study showed that when compared to healthy control skin tissues, the expression of the CXCR1 gene was obviously elevated in keloid tissues, and a novel missense mutation was identified by the sequence analysis 55 .…”
Section: Genetic Susceptibility and Genetics Of Keloidsmentioning
confidence: 99%
“…a wound healing assay was used to analyze the migratory ability of HKFs. Briefly, the fibroblasts were seeded into 6-well culture plates at a density of 1x10 6 cells/well and transfected with si-runx2 or si-nc for 24 h at 37˚C. A scratch was created using a sterile 200-µl pipette tip in the cell monolayer upon the fibroblasts reaching 95-100% confluence.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Briefly, HKFs were seeded into 6-well plates at a density of 1x10 6 cells/well and incubated for 12 h at 37˚C. Cells were transfected with si-Runx2 or si-NC for 24 h at 37˚C, subsequently harvested (300 x g; 5 min at 37˚C), washed with PBS and resuspended with 200 µl the Annexin V-PI binding buffer at a final density of 2x10 6 Statistical analysis. Statistical analysis was performed using GraphPad Prism version 8.0.1 software (GraphPad Software, inc.) and all data are presented as the mean ± Sd.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
See 1 more Smart Citation